PENGARUH SIKAP, MINAT, MOTIVASI, DAN GELAR AKUNTAN TERHADAP KEPUTUSAN MENEMPUH PENDIDIKAN PROFESI AKUNTANSI (PPAk) DI UNIVERSITAS MUHAMMADIYAH METRO - Yuniarti, Eti (Universitas Muhamamdiyah Metro, 2016)
Accounting profession education is expected to answer the needs of the importance of human resources and competent professionals in the field of accounting. Keeping in following the requirements of the accounting profession education is SI Accounting undergraduate, or graduate D-IV Department of Accounting, hence the need for attitude, interest and motivation of students studying accounting to the accounting profession. With the attitudes, interests, and motivations, expected growth accounting student wishes to study the accounting profession, which in turn will give birth to a professional public accountants. Accounting students decision to study the accounting profession, not in spite of various factors, both factors of student self (internal), as well as external factors (external). Internal factors among which is the attitude, interest, and motivation. While external factors, namely the title of accountant.The purpose of this study is the first, provide empirical evidence influence attitudes toward education profeesi accounting decisions (PPAk), both provide empirical evidence Effect of interest to decision akuntasni professional education (PPAk), third provides empirical evidence motiasi influence on the decision akuntasni professional education ( PPAk), kempat provide empirical evidence of the effect of accounting degree to decision akuntasni professional education (PPAk).Keywords: Attitudes, Interests, Motivation, Degree Accountant, Accounting Professional Education